Interfaces and interface conditions - Späth, Andreas, 1964- (Language, context, and cognition ;, 2007)
The volume comments on different interfaces between linguistic and extralinguistic knowledge. The articles analyze the conditions under which the linguistic structure of an utterance provides its interpretation in a given context, while the authors look at the conditions that hold for the transformation of a conceptual represented message into the linguistic structure. For every natural language, this process depends on its grammatical system. The authors discuss the problem from the lexical, semantic, syntactic and prosodic points of view. In addition, the volume debates questions of the repr.